Metformin combined with local irradiation provokes abscopal effects in a murine rectal cancer model - Tojo, Mineyuki; Miyato, Hideyo; Koinuma, Koji; Horie, Hisanaga; Tsukui, Hidenori; Kimura, Yuki; Kaneko, Yuki; Ohzawa, Hideyuki; Yamaguchi, Hironori; Yoshimura, Kotaro; Lefor, Alan Kawarai; Sata, Naohiro; et al. (Scientific reports, 2022)
Although preoperative chemoradiation therapy can down-stage locally advanced rectal cancer (LARC), it has little effect on distant metastases. Metformin exerts an anti-cancer effect partly through the activation of host immunity. LuM1, a highly lung metastatic subclone of colon 26, was injected subcutaneously (sc) in BALB/c mice and treated with metformin and/or local radiation (RT). Lung metastases and the primary tumors were evaluated and the phenotypes of immune cells in the spleen and lung metastases were examined with flow cytometry and immunohistochemistry. Local RT, but not metformin, partially delayed the growth of sc tumor which was augmented with metformin. Lung metastases were unchanged in metformin or RT alone, but significantly reduced in the combined therapy. The ratios of splenic T cells tended to be low in the RT group, which were increased by the addition of metformin. IFN-γ production of the splenic CD4(+) and CD8(+) T cells was enhanced and CD49b (+) CD335(+) activated NK cells was increased after combined treatment group. Density of NK cells infiltrating in lung metastases was increased after combination treatment. Metformin effectively enhances local and abscopal effects of RT though the activation of cell-mediated immunity and might be clinically useful for LARC.